Refractory Gastroesophageal Reflux Disease: Scopes Beyond PPI (Journal of Dhaka Medical College, 2023)
Gastroesophageal reflux disease (GERD) is a very common GI disorder where the reflux of gastric contents into the esophagus causes symptom generation. PPI is the principal weapon to fight against GERD. An empiric course of PPI therapy is a cost-effective strategy for managing GERD. But sometimes, PPI can only do so much if taken correctly. As PPI does not reduce the number of reflux, other measures, including lifestyle modification, are required to get relief of GERD symptoms. Most patients respond to 8 weeks of PPI therapy, but 20-40% do not respond or respond partially. While these patients are labeled as having refractory heartburn, many do not have GERD or have not been treated adequately. So, alternative etiology must be considered when patients are refractory to PPI. Endoscopy of upper GIT should be done initially in case of the presence of alarm symptoms and when considered refractory to exclude other conditions. If endoscopy reveals no abnormality, then esophageal function tests like esophageal manometry, 24 hrs ambulatory pH monitoring, and mucosal impedance test can be considered to exclude other related conditions. Endoscopic and surgical treatment options can also be considered in particular cases.J Dhaka Med Coll. 2022; 31(1) : 148-157